2014
DOI: 10.1186/1471-2474-15-395
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive series of 226 journey bicruciate substituting total knee replacements: early complication and revision rates

Abstract: BackgroundThe Journey bicruciate substituting (BCS) total knee replacement (TKR) is intended to improve knee kinematics by more closely approximating the surfaces of a normal knee. The purpose of this analysis was to address the safety of Journey BCS knees by studying early complication and revision rates in a consecutive case series.MethodsBetween December 2006 and May 2011, a single surgeon implanted 226 Journey BCS total knee prostheses in 191 patients (124 women, 67 men) who were eligible for study. Mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 21 publications
2
29
1
Order By: Relevance
“…This in contrast to stiffness rates with the original BCS I design of 22.6% [7], 2.7% [6], and 2.2% [4] reported in the literature. It remains unclear whether the absence of stiffness in our series was supported by the kinematic rotational alignment obtained using an extension-first surgical technique.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…This in contrast to stiffness rates with the original BCS I design of 22.6% [7], 2.7% [6], and 2.2% [4] reported in the literature. It remains unclear whether the absence of stiffness in our series was supported by the kinematic rotational alignment obtained using an extension-first surgical technique.…”
Section: Discussioncontrasting
confidence: 56%
“…The extension-first technique we employed may be more forgiving with guided-motion implants in comparison with the measured resection or tibia-first technique, the latter of which has been associated with midflexion instability in a recently published study in 226 consecutive knees [4]. The tibia-first technique may lead to femoral component malrotation in patients with preoperative deformities that result in ligamental instabilities [9, 18] and is furthermore associated with postoperative joint line elevation [4]. Both component malrotation and joint line elevation are risk factors for midflexion instability [15, 19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4] However, it has also been reported that normal knee kinematics and function are not accurately reproduced in traditional TKA designs. [5][6][7][8][9][10] As the demand and frequency of TKA grow, the degree of satisfaction reported is relatively low. 4, 6,11 One potential cause may be that conventional TKA designs cannot reproduce normal knee kinematics and function due to the lack of the anterior cruciate ligament (ACL).…”
mentioning
confidence: 99%